Fluorinated graphene/sulfur hybrid cathode for high energy and high power density lithium primary batteries. Issue 23 (3rd April 2018) - Peng, Sikan; Yan, Shaojiu; Wang, Nan; Nan, Wenzheng; Wang, Jixian; Chen, Xiang; Wang, Chen; Qi, Xin; Dai, Shenglong
Abstract : Fluorinated graphene (FG)/sulfur hybrid cathode with monoclinic sulfur enables the lithium primary battery exhibiting excellent capacity and rate performance. Abstract : It is a great challenge to obtain high performance carbon fluoride (CF x ) cathodes with high specific capacity and good rate performance due to the electronic conductivity of CF x being known to decrease with an increase in the specific capacity. Herein, we propose a novel fluorinated graphene (FG)/sulfur hybrid cathode to enhance both the energy density and power density of lithium/carbon fluoride (Li/CF x ) batteries. Impressive enhancements of the specific capacity, discharge voltage, and rate capability are demonstrated with the novel FG/sulfur hybrid cathode. In comparison with the pristine FG cathode, the hybrid cathode exhibits higher electrochemical activity, lower overpotential, and faster ion transfer over the main discharge range. Furthermore, when the melt-diffusion method is used to prepare the hybrid cathode, the uncommon monoclinic sulfur is presented under ambient temperature. A significant synergistic effect which reduces the reaction resistance effectively is demonstrated with the presence of monoclinic sulfur, leading to the highest energy density of 2341 W h kg −1 and a power density up to 13 621 W kg −1 at 8.0 A g −1 . Our results are expected to introduce a new generation of high energy and high power density lithium primary cells, based on a simple and effective strategy employing FG/S hybrid cathodes.